Dampak Kebijakan Perguruan Tinggi Negeri Badan Hukum (PTN BH) yang Mengakibatkan Munculnya Komersialisasi Pendidikan - Khanan Saputra (Departement of Mathematics Education, 2023)
Education in the realm of public tertiary institutions is the choice for many people, this is seen because public tertiary institutions are more prestigious than private tertiary institutions. State universities are also known for their good quality of education compared to private universities, even though not all private universities are lower in position than state universities, there are also many private universities whose quality of education is already good and commensurate with state universities. However, state universities are not without problems regarding their education, the birth of the Legal Entity State University (PTN BH) policy seems to indicate new problems for candidates and students. The publication of PTN BH has brought a new issue to the surface regarding the commercialization of education in the realm of state universities, this problem has an impact on underprivileged students due to the high costs of education. Because of these issues, here the researcher intends to describe problems regarding the commercialization of education in Legal Entity State Universities with existing data.